Extraction and partial characterization of venom from the Colombian spider Pamphobeteus aff. nigricolor (Aranae:Theraphosidae) (2013)
We report the first studies of characterization and extraction of the Pamphobeteus aff. nigricolor (Pocock, 1901) (Aranae:Theraphosidae) venom done in Colombia using the electro-stimulation technique previous anesthesia with isofluorane. After each extraction process, a low viscosity, colorless venom was obtained. This venom showed a 1.01 mg/µl density and a pH of 5. The humidity percentage did not show a significance difference between males and females (P > 0.05) with a general media of 77.49 ± 1.74%. In all cases the venom yielded was variable between males and females, with a media of 22.45 ± 5.17 mg (wet weight) and 4.58 ± 0.94 mg (dry weigh), obtaining larger amounts in females, 28.34 ± 7.49 mg and 5.69 ± 1.36 (wet and dry weight respectively). Venom showed a hemolytic activity dependent of enzymatic active phospholipase and neither coagulant nor proteolytic activities were observed. Electrophoretic profile showed a main protein content with a molecular mass below 14 kDa. RP-HPLC venom profile revealed a difference among male and female venom's content where 17 and 21 main fractions were obtained respectively. Three peptides, Theraphotoxin-Pn1a, Theraphotoxin-Pn1b and Theraphotoxin-Pn2a, were identified using HPLC-nESI-MS/MS. These peptides showed a high identity with other peptides found on Theraphosides which are proved to affect voltage-gated calcium channels. © 2013 Elsevier Ltd. All rights reserved.